New Contributions to The Chronology of The Prehispanic Occupation of The Eastern Piedemonte of The Sierra San Javier (Tucumán-Argentine): First Absolute Dates - Caria, Mario Alejandro (2020)
Among the pending issues in the archeology of the lowlands ofthe province of Tucumán, the construction of chronologies basedon absolute dates stands out, which allows the elaboration of morereliable pre-Hispanic occupation sequences to have a more precisetemporal control of local social developments. Despite havingregistered dozens of archaeological sites in these jungle and forestenvironments, most of them do not have absolute dates.